OPTIMIZATION OF SOAP PRODUCTION USING MANGO PEELS ASH AS ALKALI SOURCE - Okunola, Oluwole J.; Siaka, A. A.; Abdulkareem, O. A. (FUDMA Journal of Sciences, 2023)
The use of mango peels ash as alkali source for soap production was examined. The blends of oils used comprised of Palm Kernel Oil (PKO) and Beef Tallow (BT) oil mixtures in the ratios of 3:1,1:1 and 1:3 and the physicochemical characterization of the oil blends were analyzed. The soaps were prepared using the oil blends (PKO:BT) and alkali extract from mango peels ash using standard methods and by varying the proportions of the oil blends and the alkali extract in the ratios of 1:1, 1:2 and 2:1. The soaps produced were analysed by testing its yield, foam ability, foaming stability, total fatty matter (TFM), total fatty acid (TFA), free caustic alkali (FCA) and free carbonate alkali. The alkali content and pH of the mango peel ash extract were found to be 12.13g/dm3 and 10.9 respectively. From the varying proportions of the oil mixture, the soaps produced from PKO:BT in the ratio 1:3 showed optimum soap yields at 85.1%, 85.8% and 83.7% for oil blends and alkali extract in the ratios of 1:1, 1:2 and 2:1 respectively and are the most economical for the soap production process. However, the soaps produced from PKO:BT in the ratio 1:1 showed very good properties with the highest values for foam ability and foam stability at 21.50 ml and 7.35 mins respectively.